Desarrollo de una herramienta informática para el análisis de precios unitarios en sistemas de distribución - Tonato Espín, Rubén Darío (2022)
When exist project developments in distribution networks, unit price analyzes are being organized without a unified system. This project is developed a computer tool for the unit prices analysis in distribution networks. In the first instance, it was made an elements bibliographical compilation, what comprise an APU (Unit Price Analysis), conformed structures in the construction Agency for the Regulation and Control of Non-Renewable Energy and Natural Resources (ARCERNNR) units. Then, it was created a structures database based on their voltage level and the fuction. With a pre-established design, it was came from interfaces with the GUI tool and after this, it is generated an installation folder by using Matlab´s AppDesigner.